Desempenho de escolares com dislexia e transtorno do déficit de atenção e hiperatividade nos processos de leitura - Oliveira, Adriana Marques de [UNESP]; Cardoso, Monique Herrera [UNESP]; Pinheiro, Fábio Henrique [UNESP]; Germano, Giseli Donadon [UNESP]; Capellini, Simone Aparecida [UNESP] (My University, 2011)
This study aimed to characterize and to compare the performance of students with an interdisciplinary diagnosis of dyslexia and attention deficit hyperactivity disorder (ADHD) in students with good academic performance on the reading processes. Sixty students from both genders, from 2nd to 4th grades of municipal public schools in Marília - SP participated in this study, they were distributed as follows: GI, 20 students with interdisciplinary diagnosis of dyslexia; GII, 20 students with ADHD and GIII, 20 students with good academic performance, paired according to gender, age and grade level with GI and GII. The students were submitted to the application of the assessment of reading processes (PROLEC) composed by four processes: letters identification, lexical, syntactical and semantic. The results highlighted that the students of GIII showed superior performance comparing with GI and GII. There was difference between GI and GII only in low frequency word reading and non words reading of the lexical process. The inferior performance from GI and GII in the PROLEC tests can be justified by the difficulty on the coding and decoding abilities. In ADHD students this difficulty was due to impaired interaction between the visual, linguistic, attention and auditory processing and in the dyslexic students was due to failure at the phonological mediation process, which depends on the knowledge of rules of grapheme - phoneme conversion to the acquisition of word reading. These changes affect the reading achievement and the comprehension of the read text.

Este estudo tem por objetivos caracterizar e comparar o desempenho de escolares com diagnóstico interdisciplinar de dislexia e TDAH com escolares com bom desempenho acadêmico nos processos de leitura. Participaram 60 escolares de ambos os gêneros, de 2ª a 4ª série do ensino fundamental, divididos da seguinte forma: GI, 20 escolares com dislexia; GII, 20 escolares com TDAH, e GIII, 20 escolares com bom desempenho acadêmico, pareados segundo gênero, faixa etária e escolaridade com o GI e o GII. Os escolares foram submetidos à aplicação das provas de Avaliação dos Processos de Leitura - PROLEC, composta pelos processos de identificação de letras, léxico, sintático e semântico. Os resultados evidenciaram que os escolares do GIII apresentaram desempenho superior em relação ao GI e ao GII. Os escolares do GI e do GII apresentaram diferença estatisticamente significante apenas nas provas de leitura de palavras não frequentes e leitura de não palavras do processo léxico. A dificuldade apresentada pelo GI e pelo GII nas provas do PROLEC pode ser justificada pela dificuldade de codificação e decodificação de símbolos. Nos escolares com TDAH, essa alteração se deve ao comprometimento da interação entre o processamento visual, linguístico, atencional e auditivo, e nos escolares com dislexia é em decorrência de falha no processo de mediação fonológica, que depende da utilização do conhecimento das regras de conversão grafema-fonema para a construção da leitura da palavra. Essas alterações comprometem a realização da leitura e a compreensão do material lido.
Performance of students with dyslexia and attention deficit disorder with hyperactivity in the reading assessment processes
Keywords: Leitura; Dislexia; Transtorno do Déficit de Atenção e Hiperatividade